IMPACT OF LOGISTICS EFFICIENCY ON THE ECONOMY - Egamberdiev Shavkatbek Shakhobiddin ugli; Ibragimova Gulnozakhan Sayidmurodovna (Лучшие интеллектуальные исследования, 2024)
Annotation. In addition to revealing the impact of logistics efficiency on the economy, this article also provides information on the world-class role of the logistics industry of Uzbekistan, why improving the efficiency of logistics is relevant today, and the role of Uzbekistan as a transit state. Further considerations have been made to further improve the economy by improving logistics efficiency.